Body mass index and bioelectrical vector distribution in 8-year-old children - Guida, Bruna; Pietrobelli, Angelo; Trio, Rossella; Laccetti, Roberta; Falconi, Claudio; Perrino, Nunzia Ruggiero; Principato, Silvestre; Pecoraro, Pierluigi (Nutrition, metabolism, and cardiovascular diseases, 2008)
To describe bioelectrical impedance vector distribution in relation to BMI (body mass index; body weight/stature 2) in a population of healthy children in order to detect possible changes in body composition status. Observational study involving 464 healthy 8-year-old children. The subjects were divided into three groups based on their BMI: 218 normal weight (NW) children with BMI < 18.4 for male and BMI < 18.3 for female; 135 overweight (OW) children with BMI 18.4 to <21.6 for male and with BMI 18.3 to <21.6 for female; 111 obese (OB) children with BMI ≥ 21.6. Skinfold thickness was measured at the triceps using a Holtain caliper. Bioelectrical impedance analysis (BIA) measurements were performed. Total body water (TBW), fat-mass (FM), fat-free mass (FFM), body cell mass (BCM) and extra-cellular water (ECW) were estimated using conventional BIA regression equations. The resistance–reactance graph (RXc graph) method was used for vector BIA using as reference population the set of 353 children with BMI 14.0–21.5 kg/m 2. Mean vector displacement followed a definite pattern, with progressive vector shortening in groups with increasing BMI class, and along a fixed phase angle. This pattern indicates an increase in TBW due to an increase in soft tissue mass with an average, normal hydration. In NW children, vectors out of the right and upper half of the 75% tolerance ellipse indicating leanness, and vectors falling out of the right and lower half of the tolerance ellipse indicating undernutrition, show a significantly reduced value of BCM but no significant differences in FM or triceps skinfold thickness (TST), respectively, compared to vectors falling within the 75% tolerance ellipse. Although BMI is a reliable measure to grade overweight, it cannot differentiate whether weight change is due to variation of FM, FFM or water. In our study a different impedance vector pattern has been associated with normal weight to obesity, and we have established the trajectory followed by the impedance vector of standardized age, healthy children grouped by BMI. This BIVA may be useful for clinical purposes due to ability to detect changes in hydration or body composition in children.